Tümėn Zasagt Haan = Tümen ǰasaġtu qaġan - Hišigt, Norovsambuugijn ("Mongolyn 100 haan, najman bogd" 108 botʹ cuvral = "Mongġol-un 100 qaġan, naiman boġda" cubural, 2002)
Biography of Tu̇mėn Zasagt Khaan, 1539-1592, Mongolian ruler